Peran Dan Pengaruh dari Gaya Dasar Kepemimpinan dalam Organisasi Pendidikan Menurut Buku Teori Organisasi - Pratama, M. Arya; Mulyadi, Mulyadi; Ningrum, Yessy Prasetya; Rizki, Natasya; Prandika, Noval Dwi; Panca, Anne; Annisa, Windi Fitri; Mabel, Nadira (Indo-MathEdu Intellectuals Journal, 2025)
Leadership plays a central role in determining the direction and success of educational organizations. This article aims to examine the role and influence of various basic leadership styles in the context of educational organizations, as explained in the Organizational Theory Book. This study is conducted using a literature review method by analyzing various leadership theories and approaches, such as democratic, authoritarian, laissez-faire, situational, transactional, and charismatic styles. The results of the study indicate that each leadership style has its advantages and limitations depending on the situation, the characteristics of the individuals being led, and the organizational culture. Leaders who are able to adapt their leadership style contextually are more effective in building communication, improving performance, and creating a productive and harmonious work environment. The implications of this finding suggest that a deep understanding of leadership styles and their appropriate application is key to supporting the sustainable achievement of the vision and mission of educational institutions.